CONCURRENT INFECTION OF SALMONELLA HEPATITIS IN LAKHIMPUR DISTRICT OF ASSAM - JITENDRA SHARMA, (International Journal of Pharma and Bio Sciences, 2014)
Hepatitis A is a serious liver disease caused by the hepatitis A virus which occurs globally and is causing a public health concern, primarily in developing countries. In tropical endemic areas like India common mode of transmission for both enteric fever and hepatitis A are mostly through Feco-oral route. The objective of the study was to find out the source of infection as well as descriptive epidemiological analysis in terms of time, place and person during an outbreak of Hepatitis A in Lakhimpur district of Assam. 2-3 ml of blood samples were collected from suspected viral hepatitis patients followed WHO case definition. The samples were further processed for detection of Malaria (microscopic slide), Hepatitis A &E IgM (Elisa), Typhoid (Widal and Typhi dot) and Leptospira (IgM Elisa).Water samples collected from the drinking water source for H2S and Most probable number (MPN) test. We identified 56 cases with two deaths. 48.21% of collected samples showed HAV IgM positive whereas no HEV IgM positive cases found. Likely no Malaria and Leptospira cases were detected among the suspected viral hepatitis cases. But, it was observed that 7.40% of the samples showed mixed infection of Salmonella and HAV. 91% of the collected water sample showed H2S positive.MPN result also revealed that those drinking water source used by the people were contaminated with high quantity of bacilli and not suitable for drinking purpose.